Impact of Micro Teaching Program on English Education Fresh Graduates' Teaching Skills - Apriani Shinta; Eryansyah Eryansyah (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
Microteaching must give important teaching skills to EFL students. Some studies have investigated its impact on EFL students’ teaching skills but no study has been focused on fresh graduates. This study was a descriptive qualitative study with the aim to find out the impact of micro teaching on teaching skills of the fresh graduates of the English Education study program of Sriwijaya University. The participants were six of the fresh graduates in English Education study program of Sriwijaya University. The instruments were a questionnaire on Google Form and a semi-structured interview. The collected data were analyzed descriptively in the form of percentages for the questionnaire and the data from interview were analyzed through the methods of data reduction, data display, and conclusion drawing or verification. The findings showed that the microteaching class had given positive impacts on the teaching skills of the fresh graduates. The program improved the teaching skills and teaching set such as (lesson plan, material, teaching media, students’ worksheet and assessment. It also enhanced the way the class is managed and handled effectively, including how to open and close it. To put it briefly, this program helped freshly graduated students adjust to life in the real classroom.